Paradigms of Smart and Intelligent Communication, 5G and Beyond - Rai, Amrita; Kumar Singh, Dinesh; Sehgal, Amit.; Cengiz, Korhan (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book focuses on both theory and applications of Artificial Intelligence and Machine Learning in the broad areas of communication and networking. This book focuses on the ongoing research work and future scope for various open research issues related to sustainable design, development, and analysis of smart communication, 5G and beyond, with the integration of Artificial intelligence and IoT. It addresses fundamental technology components for 5G and beyond, which include modern advancements in communication and networking in a real-world application. The book presents the convergence of Artificial Intelligence, Machine Learning, and IoT with 5G and beyond wireless networks to give some ice-breaking solutions in radio resource allocation, network management, and cybersecurity. This book will be a valuable resource for academicians, researchers, and professionals working in artificial intelligence/machine learning and its applications in communication and 5G.
Artificial Cognitive Computing for Smart Communications -- Green IoT using Machine Learning, Deep Learning Models for 5G Networks -- Integration of IOT and 5G Communication -- Role of IoT in Smart Communication and 5G using Antenna Array -- Applications of Deep Reinforcement Learning in Wireless Networks -- Detection of Consumption of Alcohol Using Artificial Intelligence -- Analysis of Finger Vein Pattern Recognition Technique using Machine Learning -- Machine Learning Techniques for Anomaly Detection -- Application of AI & ML in 5G Communication -- Software Defined Network-based Management Architecture for 5G Network -- Reversible Logic Based Single Layer Flip Flops and Shift Registers in QCA Framework for the Application of Nano-communication -- Machine Learning Technique for Few-mode Fiber Design with Inverse Modelling for 5G and Beyond -- IoT for Landslides: Applications, Technologies and Challenges -- A Review: Dust Cleaning Approach of Solar Photovoltaic System Using Emerging Technology -- Prediction of Heart Disease Using Hybrid Machine Learning Technique.
Keywords: Artificial intelligence; Machine learning; Telecommunication; Artificial Intelligence; Machine Learning; Communications Engineering, Networks